Analisis Permasalahan Belajar Siswa dari Sudut Pandang Filsafat Pendidikan: Studi Kasus di MTs Muhammadiyah 7 Klego Boyolali - Mujibburrohman, Mujibburrohman; Sarwanto, Sarwanto (TSAQOFAH, 2026)
The success of the teaching–learning process is indicated by the achievement of student competencies encompassing knowledge, skills, and attitudes; however, in practice, various learning difficulties still arise among students at MTs Muhammadiyah 7 Klego Boyolali. This study aimed to describe students’ learning difficulties from the perspective of the philosophy of education by highlighting causal factors and the philosophical characteristics of understanding the educational process. The research employed a library study method based on bibliographic sources from relevant books and scholarly journal articles, complemented by field-based observations of students at MTs Muhammadiyah 7 Klego Boyolali. The findings show that the factors causing students’ learning difficulties are grouped into two categories: internal student factors, including low intellectual capacity, emotional and attitudinal instability, and sensory impairments related to vision and hearing; and external student factors originating from the family, community, and school environment. From a philosophical perspective on education, the discussion of learning difficulties is connected to the characteristics of the philosophy of education, which encompass theories of education, theories of learning, theories of learners, and theories of educators as a conceptual foundation for understanding and addressing learning problems at a more fundamental level. These findings affirm that addressing learning difficulties requires an approach that is not only technical–pedagogical in nature but is also rooted in a comprehensive philosophical framework of education concerning the nature of education, learners, and the learning process.